Decoding Innocence in the Israeli-Palestinian Conflict: Semiotics of Palestinian Children's Cartoons on Twitter - Salinayanti, Salim; Sharifah Hayaati, Syed Ismail (Shahid Chamran University of Ahvaz, 2025)
Following the October 7, 2023 attacks in Israeli-Palestinian conflict zones, social media, especially Twitter, saw a spike in cartoon sharing. This study examines the visual representation of Palestinian children in cartoons on Twitter to decode the perspectives of child characters within the broader contexts of conflict and innocence. The study employed social identity theory (SIT) to frame the children’s innocence shown in the cartoons. Visual content for this qualitative study on Palestinian children's cartoons was collected from Twitter. Data were counted for frequency, categorised into themes, and analysed using Barthes’ semiotic framework. Findings reveal 6 themes: Victimhood, Emotional Appeal and Social Responses, Cultural Context: Displaced Histories, Political Commentary, Resilience and Resistance, and Unaligned Representation. The predominant theme of Victimhood in the Palestinian children's cartoons underscores their vulnerabilities within the Israeli-Palestinian conflict. The discovery of Unaligned Representation in this study indicates a recontextualisation of diverse perspectives that challenge singular narratives.